RISE: Green retrofit framework for sustainable residential refurbishment project / Ts Dr Julitta Yunus and Siti Aishah Ramli - Yunus, Julitta; Ramli, Siti Aishah (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
Malaysia is becoming heavily dependent on energy due to rapid development and industrialization, resulting in a significant increase in GHG emissions. Rapid urbanization has remarkably turned Malaysia into one of the most urbanized nations in Asia (World Bank, 2021). Over the past years of dedication to economic development, the country has shown an increase in the number of existing buildings, with residential as a leading sector.